Determination of halogenated acetic acids and 2,2-dichloropropionic acid in water samples - Clemens, Markus; Schöler, Heinz Friedrich (Fresenius' journal of analytical chemistry, 1992)
A new method is described for the determination of halogenated acetic acids and 2,2-dichloropropionic acid in slightly polluted water. The acids were extracted in a light-phase rotary perforator, derivatised with diazomethane and determined by GC-ECD and GC-MS. The standard deviations were in the range of 14.5-16.8%. Average recoveries were 82%, 92% and 79% for monochloro-, dichloro- and trichloroacetic acid, respectively. The extraction yields for the bromoacetic acids and dichloropropionic acid were in the range of 64-85%.
Gesehen am 04.04.2023